БЎЛАЖАК ИНГЛИЗ ТИЛИ ЎҚИТУВЧИЛАРИДА НУТҚ ФАОЛИЯТИНИНГ ГРАММАТИК КЎНИКМАЛАРИНИ ШАКЛЛАНТИРИШ - Жуманазаров, У.У. (SCIENCE and SOCIETY, 2021)
The article discusses the linguistic, methodological and psychological components of the content of teaching the grammar principals of speech in a foreign language, as well as the stages of formation of grammatical skills in future English teachers.
Keywords: speech; grammar; skill; component; knowledge; communication; ability; linguistics; methodology; psychology